Development of a human-size magnetic particle imaging device for sentinel lymph node biopsy of breast cancer - Shi Bai; Shi Bai; Lingke Gai; Qinyang Zhang; Yue Kang; Zhiyao Liu; Yuan He; Yuan He; Wenzhong Liu; Tao Jiang; Zhongzhou Du; Siyao Du; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
In this study, a novel human-size handheld magnetic particle imaging (MPI) system was developed for the high-precision detection of sentinel lymph nodes for breast cancer. The system consisted of a highly sensitive home-made MPI detection probe, a set of concentric coils pair for spatialization, a solenoid coil for uniform excitation at 8 kHz@1.5 mT, and a full mirrored coil set positioned far away from the scanning area. The mirrored coils formed an extremely effective differential pickup structure which suppressed the system noise as high as 100 dB. The different combination of the inner and outer gradient current made the field free point (FFP) move in the Z direction with a uniform intensity of 0.54T/m, while the scanning in the XY direction was implemented mechanically. The third-harmonic signal of the Superparamagnetic Iron Oxide Nanoparticles (SPIONs) at the FFP was detected and then reconstructed synchronously with the current changes. Experiment results showed that the tomographic detection limit was 30 mm in the Z direction, and the sensitivity was about 10 μg Fe SPIONs at 40 mm distance with a spatial resolution of about 5 mm. In the rat experiment, 54 μg intramuscular injected SPIONs were detected successfully in the sentinel lymph node, in which the tracer content was about 1.2% total injected Fe. Additionally, the effective detection time window was confirmed from 4 to 6 min after injection. Relevant clinical ethics are already in the application process. Large mammalian SLNB MPI experiments and 3D preoperative SLNB imaging will be performed in the future.